KONSTRUKSI IDENTITAS BUDAYA KEINDONESIAAN DALAM WACANA BUKU TEKS SEKOLAH DASAR - Anshori, Dadang (Jurnal Pendidikan Bahasa dan Sastra, 2016)
AbstractThe objectives of  research are identified the Indonesia culture identity constructed in primary schools textbooks with curriculum 2013. The Indonesia culture identity was very important while considering social conflict today very apraid and doing in every social life dimention. The conflict was become between scholar social community also unscholar social community with be at the bottom of variation. The study used text content analysis through words and sentence as based analysis. The analysis of data are discourse of textbooks grade one primary schools amounted four theme.  The research finding that  textbooks represented Indonesia culture identity in all activity and the action has doing by the stories actor which are cheave to each action as well setting as planning of writer textbooks. The language used as Indonesia identity representation described  in words and sentence or discourse as well depicted identity. The Indoensia culture identity has description e.g. religious identity, humanism, socialism, sportive, toleration, works in together, discipline, optimist, and rational. The ideology has making in textbooks based on ideology reliogius, social-humanism ideology, toleration-pluralism ideology, and independenty ideology.Keywords: contruction, grammar, identity, ideology, discourse, textbook